Comparative Analysis of Android 10 and Android 14 in the Eventeer Application - Aris Pratama; Rendi Panca Wijanarko; Putu Anggi Suryantari (IJCONSIST JOURNALS, 2024)
In this era of rapid technological advancement, event management systems have undergone significant transformation towards mobile-based models. One prominent application in this domain is Eventeer, offering features such as in-app chat, event scheduling, learning media, and event feeds for user interaction. This study aims to compare the performance of Android operating system versions 10 and 14 when running the Eventeer application. Performance measurements include memory usage, CPU utilization, and total storage used. Testing was conducted using Android Profiler in Android Studio to obtain accurate and comprehensive data. Results indicate that Android 14 exhibits higher memory usage compared to Android 10, while CPU usage tends to be more efficient on Android 14. The application size and storage usage did not show significant differences between the two Android versions. These findings provide valuable insights for developers and users on how the performance of the Eventeer application may be influenced by the Android OS version used. The study recommends further research encompassing broader test aspects such as battery consumption and network usage. Thus, future research can provide deeper insights into the factors affecting the performance of Android operating systems on mobile applications like Eventeer.